Lusosex : gender and sexuality in the Portuguese-speaking world - Quinlan, Susan Canty, 1948-; Arenas, Fernando, 1963- (University of Minnesota Press, 2002)
Challenging static notions of sexualities within the Portuguese-speaking world, these essays expand our understanding of the multiplicity of differences and marginalized subjectivities that fall under the intersections of sexuality, gender, and race.